Oil and water cooperative security in the Persian Gulf - Moller (I.B. Tauris Publishers, 2001)
This collection of work by experts from the Persian Gulf region, Europe and the USA covers the theoretical foundations in the international relations of the region and suggests pragmatic solutions to the security problems of the Persian Gulf states stemming from the question of water resources.